The Main Tendencies of Contemporary Political Linguistics in Russia - Chudinov, Anatoly (Respectus Philologicus, 2003)
The present research investigates the main tendencies of Political Linguistics in modern Russian based on the following oppositions:research in the theory of Political Linguistics – description of separate elements of the language of politics;chronological framework of investigation: Soviet or post-Soviet epoch;different levels of analysis: vocabulary, phonological system, word-building, morphology, syntax, text and discourse;normative approach – descriptive approach which implies pure record and study of new phenomena without their estimation;research of different political genres, narratives and texts or study of some features common to the language of politics;investigation of the idiostyle of some political leaders, political trends and parties or study of some regularities of the language of politics;discourse analysis of communicative roles, rituals, strategies and tactics, i.e. the language of politics under investigation;use of the methods of psycholinguistics, cognitive science, sociolinguistics, cultural linguistics, structuralism and others;study of Russian political speech – comparative research of political discourse of different countries and epochs;special investigations in the sphere of Political Linguistics – material of Political Linguistics taken from works of other scientific fields.
Keywords: linguistics; politics; Russian; language; speech; text; genre; style; discourse